Tattooing, Piercing, Drug Use and Their Associations with Sexually Transmitted Infections among Young Men Who Have Sex with Men - Mona Safitri Fatiah; Afwan Syarif; Muhammad Ruslan; Yane Tambing (Jurnal Ilmiah Kesehatan Masyarakat : Media Komunikasi Komunitas Kesehatan Masyarakat, 2025)
Background: Young men who have sex with men in Indonesia face a high vulnerability to sexually transmitted infections. However, evidence on the role of body modification and drug use remains limited. This study examined behavioral correlates of self-reported sexually transmitted infection symptoms. Methods: Data were obtained from the 2018–2019 Integrated Biological and Behavioral Survey, a cross-sectional respondent-driven sampling study involving 1,988 men aged 18–24 years across multiple Indonesian cities. Weighted logistic regression was used to estimate adjusted odds ratios for sexually transmitted infection symptoms in relation to tattooing, piercing, drug use, condom use, HIV prevention knowledge, and sociodemographic factors. Results: The prevalence of self-reported sexually transmitted infection symptoms was 22.8%. Tattooing, piercing, and drug use were not independently associated with these symptoms after adjustment. In contrast, low human immunodeficiency viruses (HIV) prevention knowledge (Adjusted OR = 8.53; 95% CI: 2.38–30.4) and inconsistent condom use (never: Adjusted OR = 32.3; 95% CI: 1.34–775.5; occasional: Adjusted OR = 3.57; 95% CI: 1.12–11.4) showed strong associations. Conclusion: The primary drivers of sexually transmitted infection symptoms among young men who have sex with men were gaps in HIV prevention knowledge and inconsistent condom use, rather than tattooing, piercing, or drug use. Interventions should prioritize sexual health education, condom promotion, and regulatory oversight for body modification practices.